2020
DOI: 10.20944/preprints202004.0247.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigallocatechin-Gallate and Theaflavin-Gallate Interaction in SARS CoV-2 Spike-Protein Central-Channel with Reference to the Hydroxychloroquine Interaction: Bioinformatics and Molecular Docking Study

Abstract: SARS CoV-2 or COVID-19 pandemic global-outbreak created the most unstable situation of human health-economy. Last two decades different parts of the word experienced smaller or bigger outbreak related to human-coronaviruses. The spikeglycoproteins of the COVID-19 (similar to SARS-CoV) attach to the angiotensin-converting-enzyme (ACE-2) and transit over a stabilized open-state for the viral-internalization to the host-cells and propagate with great efficacy. Higher rate of mutability makes this virus unpredicta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…This has been demonstrated in our previous findings on some suitable epitope-screening from SARS CoV 2 spike[23]. Our earlier study also demonstrated that Epigallocatechin gallate (EGCG) and Theaflavin gallate (TDG) are the potent binder to the CoV 2 spike channel[24]. Increased cytokines and other hematopoetic parameters (oxidative stress markers) by LPS-administration have been shown to terminate by Nigella sativa (NS) extract[25].Cardio-respiratory and endothelial dysfunction is one of the major symptoms of SARS CoV 2 infection.And this dysfunction may be counteracted by NS and its component thymoquinone by restraining interleukin-1β, TNF-α and NF-κB signaling[26].…”
supporting
confidence: 68%
“…This has been demonstrated in our previous findings on some suitable epitope-screening from SARS CoV 2 spike[23]. Our earlier study also demonstrated that Epigallocatechin gallate (EGCG) and Theaflavin gallate (TDG) are the potent binder to the CoV 2 spike channel[24]. Increased cytokines and other hematopoetic parameters (oxidative stress markers) by LPS-administration have been shown to terminate by Nigella sativa (NS) extract[25].Cardio-respiratory and endothelial dysfunction is one of the major symptoms of SARS CoV 2 infection.And this dysfunction may be counteracted by NS and its component thymoquinone by restraining interleukin-1β, TNF-α and NF-κB signaling[26].…”
supporting
confidence: 68%
“…Some recent studies have shown that catechins can be used as alternative agents in COVID-19 infection. According to Maiti and Banerjee ( 2020 ), catechins, such as epigallocatechin gallate or theaflavin gallate, interact more strongly with the amino acids of the spike protein than hydroxychloroquine. There are also some data in the literature that some catechins, such as theaflavin digallate, epigallocatechin gallate and gallocatechin gallate, inhibit the main protease of 2019-nCoV together with the spike glycoprotein (Manish, 2020 ; Peterson, 2020 ; Sayed et al., 2020 ; Tallei et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, SARS‐CoV‐2 cannot fuse with ACE2 (Abderrazak et al, 2015; Muchtaridi et al, 2020; J. W. Yu et al, 2020; Zhai et al, 2020). Baicalin, scutellarin, hesperetin, nicotianamine, glycyrrhizin (H. Chen & Du, 2020), epigallocatechin‐3‐gallate, theaflavin gallate (Maiti & Banerjee, 2021), naringenin, quercetin, luteolin (Maurya, Kumar, Prasad, Bhatt, & Saxena, 2020), fisetin, kaempferol (Pandey et al, 2020) were due to anti‐SARS‐CoV‐2 effect and to the low toxicity selected as potential candidates for COVID‐19 treatment.…”
Section: Flavonoidsmentioning
confidence: 99%